Communication factors and practices in distributed software development projects - Junior, Ivaldir Honório de Farias; Barbosa, Jefferson Ferreira; Vieira, Jeferson Kenedy Morais; Torcate, Arianne Sarmento; Silva, Dennis Sávio; Marinho, Marcelo Luiz Monteiro (Information and software technology, 2026)
Software development is increasingly being conducted across geographically dispersed teams and organizations, involving contributors from different countries, time zones, and cultural contexts. This trend toward distributed software development (DSD) reflects both globalization and the growing reliance on digital collaboration tools. At first, DSD may seem like a relatively straightforward process, but it presents several challenges for the development teams, such as: communication, cultural and linguistic differences. These challenges raise issues that require further investigation by software development researchers, particularly those focusing on DSD. In order to contribute in this context, this research aims to identify factors and practices that influence communication in DSD projects. For this, a Systematic Literature Review (SLR), covering the period from 1999 to 2023, was carried out in order to collect data from empirical studies related to communication in DSD projects. We identified 246 relevant studies across six electronic databases, 13 journals, and 16 conferences. Our results identified 37 factors and 49 practices that can positively impact communication in projects in this context.